Analysis of the impact of the covid-19 pendemic on the development of all sectors in west java - Sugiyanto Ikhsan; Udin Hidayat (Co-Value Jurnal Ekonomi Koperasi dan kewirausahaan, 2024)
This study aims to determine the impact of the COVID-19 pandemic on the development of business fields throughout the sector in West Java. The covid-19 pandemic that has spread lately caused the development of business fields throughout the sector in West Java is almost in decline. The method used in this study is a descriptive quantitative method using a secondary data analysis approach. Based on the results of research almost all business field sectors have suffered a decline there are only a few sectors that are still growing positively, in addition there are some excellent sectors that are supporting the economy of West Java such as Agriculture, forestry and fisheries sector, Information and Communication Sector and, education services sector. This is based on a comparative analysis (Moving based index) of PDRB data that has been processed to find out the development of the business field in the midst of the COVID-19 pandemic as well as LQ analysis to find out what superior sectors West Java has in the midst of the pandemic